Edukasi kesehatan: Pelatihan tanggap bencana dan simulasi gempa bumi - Agustinawati, Zulaikha; Angraini, Wulan; Wijaya, Andri Kusuma; Sartika, Andry (Poltekkes Kemenkes Kupang, 2024)
Background: Bengkulu is located between Indian Ocean and Asian tectonic plates, making Bengkulu an area prone earthquake. SMKS Muhammadiyah 9 is located on shoreline with a distance of ± 2 km making the school prone to disasters. School children are one of the vulnerable groups, having greatest risk of being affected disaster. Knowledge of teachers and students is very necessary in order as anticipatory steps need to be prepared for teachers and students. Objective: determine the effect of health education, disaster response training and earthquake simulation on student knowledge and attitudes towards earthquakes. Methods: Quantitative research with quasy experiment methods pre and post-test at SMKS Muhammadiyah 9 Bengkulu City through health education with lectures, audio-visual videos, disaster response training and earthquake simulations. Sample 52 people with purposive sampling technique. Data analysis used paired t-test. Results: the average difference in knowledge and attitudes teachers and students before and after being given health education, simulation training and earthquake simulation is 2.36 and 5.73.